Formation of NH4+at the Brønsted site in SAPO catalysts - Jumras Limtrakul (2018)
The catalytic properties of ammonia adsorption on silicoaluminophosphate (SAPO) clusters have been investigated within the framework of the ab initio self-consistent field method. Full optimization of strutures has been carried out at the DZ, DZP and TZ2P levels of theory. Two different types of ammonia adsorption on SAPO framework sites are proposed. In one of these the structures H 3 SiOHA1(OH) 2 OPH 3 ...NH 3 are stablilized on the bridging OH by a single site binding with an interaction energy of - 17.49 kcal/mol. The others is a type of the structure [H 3 SiOA1(OH) 2 OPH 3 ] [NH 4 + ], in which the ammonium cation forms two hydrogen bonds towards the unprotonated framework sites. Other possible structures like a "bifurcated" structure are less stable than the two H-bonded structures by about 0.48 and 0.1 kcal/mol at the DZP and TZ2P basis set levels respectively. This indicates the free rotation of the NH 4 + on the SAPO surface site at room temperature. The interaction energies for the structures [H 3 SiOA1(OH) 2 OPh 3 ] [NH 4 + are more stabe than for the structures H 3 SiOhA1(OH) 2 OPH 3 ...NH 3 by 0.5-1.36 kcal/mol depending on the basis sets. These calculated energy values are an inversion order from the zeolite/NH 3 complexes. Comparison of the SAPO complexes with hydrogen halides, silanol, and zeolite has demonstrated that the hydrogen-form SAPO is at least as acidic as zeolite. © 1994.